The impact of social executives on firms’ mergers and acquisitions strategies: A difference-in-differences analysis - Wang, Qiping; Lau, Raymond Yiu Keung; Xie, Haoran (Journal of business research, 2021)
Social media is an influential medium for various stakeholders in the business domain. This study focuses on the presence of “social executives,” that is, strategic leaders who actively engage in online social media, and examines their impact on corporate mergers and acquisitions (M&A) strategies. The results of our difference-in-differences (DID) analysis suggest that the presence of acquirer-side social executives improves acquirer firms’ propensity to undertake M&A transactions and boosts announcement returns. Interestingly, these relationships are more pronounced when senior executives have high behavioral engagement in online social media compared with those with low engagement. The major contribution of this study is to empirically verify the impact of the presence of social executives on corporate M&A outcomes through the lens of the upper echelons and social presence theories.